A culturally and linguistically salient pilot intervention to promote colorectal cancer screening among Latinos receiving care in a Federally Qualified Health Center. Issue 3 (30th March 2019) - Gwede, Clement K; Sutton, Steven K; Chavarria, Enmanuel A; Gutierrez, Liliana; Abdulla, Rania; Christy, Shannon M; Lopez, Diana; Sanchez, Julian; Meade, Cathy D
Abstract: Despite established benefits, colorectal cancer (CRC) screening is underutilized among Latinos/Hispanics. We conducted a pilot 2-arm randomized controlled trial evaluating efficacy of two intervention conditions on CRC screening uptake among Latinos receiving care in community clinics. Participants ( N = 76) were aged 50–75, most were foreign-born, preferred to receive their health information in Spanish, and not up-to-date with CRC screening. Participants were randomized to either a culturally linguistically targeted Spanish-language fotonovela booklet and DVD intervention plus fecal immunochemical test [FIT] (the LCARES, Latinos Colorectal Cancer Awareness, Research, Education and Screening intervention group); or a non-targeted intervention that included a standard Spanish-language booklet plus FIT (comparison group). Measures assessed socio-demographic variables, health literacy, CRC screening behavior, awareness and beliefs. Overall, FIT uptake was 87%, exceeding the National Colorectal Cancer Roundtable's goal of 80% by 2018. The LCARES intervention group had higher FIT uptake than did the comparison group (90% versus 83%), albeit not statistically significant ( P = 0.379). The LCARES intervention group was associated with greater increases in CRC awareness ( P = 0.046) and susceptibility ( P = 0.013). In contrast, cancer worry increased more in the comparison group ( P = 0.045). Providing educational materials and a FIT kit to Spanish-language preferring Latinos receiving care in community clinics is a promising strategy to bolster CRC screening uptake to meet national targets.